Construction of Judicial Interpretation In Indonesia's Criminal Justice System Regarding The Implementation of The New Penal Code - Suryana, Iyus (Indonesian Journal of Law and Justice, 2025)
Judicial interpretation within Indonesia’s criminal justice system presents a complex challenge, particularly with the implementation of the new Criminal Code (KUHP) under Law Number 1 of 2023. The new Criminal Code incorporates legal pluralism, including customary law (living law), creating a tension between the principle of legality and substantive justice. In practice, judges struggle to balance legal certainty with interpretative flexibility to align legal decisions with societal values. This study aims to analyze judicial interpretation patterns in Indonesia’s criminal justice system following the enactment of the new Criminal Code and to identify factors contributing to judicial inconsistencies. Using a normative legal approach combined with legal hermeneutics, this research examines how judges apply legal provisions through an analysis of legislation, court rulings, and relevant legal theories. The findings indicate that most judges still adhere to legal positivism, prioritizing legal certainty, although sociological and teleological approaches are increasingly applied in certain cases, particularly those involving restorative justice. However, inconsistencies in judicial rulings remain a concern due to judicial subjectivity, political pressure, and public opinion. Strengthening legal hermeneutic methodologies in judicial education and developing more binding legal precedents are essential steps to improving judicial consistency and public trust in Indonesia’s criminal justice system.